2015
DOI: 10.1089/fpd.2014.1892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Essential Oils on Germination and Growth of Some Pathogenic and Spoilage Spore-Forming Bacteria

Abstract: The use of essential oils as a food preservative has increased due to their capacity to inhibit vegetative growth of some bacteria. However, only limited data are available on their effect on bacterial spores. The aim of the present study was to evaluate the effect of some essential oils on the growth and germination of three Bacillus species and Geobacillus stearothermophilus. Essential oils were chemically analyzed using gas chromatography and gas chromatography coupled to mass spectrometry. The minimal inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…Plant-derived essential oil components (EOCs) are composed of heterogeneous mixtures of organic compounds, some volatile, that may be obtained from parts of plant tissues (e.g., buds, flowers, seed, leaves, twigs, fruits, bark, woods, and roots) by steam distillation and/or solvent extraction (Burt, 2004;Seow, Yeo, Chung, & Yuk, 2014). EOCs have been widely studied for their capabilities to inhibit the growth, or reduce numbers, of foodborne bacterial microbes in liquid and on solid foods (Lawrence & Palombo, 2009;Nazzaro, Fratianni, De Martino, Coppola, & De Feo, 2013;Nuñez & Aquino, 2012;Park, Kang, & Song, 2018;Smith-Palmer, Stewart, & Fyfe, 1998;Voundi et al, 2015). EOCs containing phenolic groups in particular are reported to exhibit antimicrobial activity against several bacterial foodborne pathogens (Rota, Carraminana, Burillo, & Herrera, 2004;Seow et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Plant-derived essential oil components (EOCs) are composed of heterogeneous mixtures of organic compounds, some volatile, that may be obtained from parts of plant tissues (e.g., buds, flowers, seed, leaves, twigs, fruits, bark, woods, and roots) by steam distillation and/or solvent extraction (Burt, 2004;Seow, Yeo, Chung, & Yuk, 2014). EOCs have been widely studied for their capabilities to inhibit the growth, or reduce numbers, of foodborne bacterial microbes in liquid and on solid foods (Lawrence & Palombo, 2009;Nazzaro, Fratianni, De Martino, Coppola, & De Feo, 2013;Nuñez & Aquino, 2012;Park, Kang, & Song, 2018;Smith-Palmer, Stewart, & Fyfe, 1998;Voundi et al, 2015). EOCs containing phenolic groups in particular are reported to exhibit antimicrobial activity against several bacterial foodborne pathogens (Rota, Carraminana, Burillo, & Herrera, 2004;Seow et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On bacterial cells, these essential oils damage cell membranes and perturb metabolic activities in bacteria. Also for spores, Voundi et al 2015 reported that essential oils of thyme suppressed the germination of spores from Bacillus cereus, B. subtilis and Bacillus megaterium.…”
Section: Figmentioning
confidence: 99%
“…In this study, essential oils contained in Product C inhibited the cells, and the cells were practically not detected after 24 h pre-enrichment at 30 • C and remained under the detection limit (0.04 log MPN/g). Voundi et al [23] demonstrated that some essential oils had a bactericidal effect on vegetative cells and an inhibitory effect on both the germination and the outgrowth of Bacillus spores. Essential oils could damage a variety of targets within bacterial cells, particularly the membrane and cytoplasm, and in certain situations the action of these oils can completely alter the morphology of the cells [24].…”
Section: Challenge In Products Without Neutralizationmentioning
confidence: 99%